ANALISA NILAI PERUSAHAAN DENGAN PENDEKATAN ECONOMIC VALUE ADDED (EVA) : Studi Pada PT. ABC Tahun 2014-2018 - Muhani Muhani (Universitas Nasional, 2019)
EVA is the answer to better research methods on the company's operational performance. This is because EVA includes the value of capital costs in its calculations to find out the addition of the company's economic value. The problem studied is how the company value when measured by the EVA approach. Based on these problems, this study aims to analyze how the value of the company is measured by the EVA approach. The data used are secondary data from internal data sources collected through document review techniques. The analytical method used is a quantitative method, namely the analysis of data in the form of numbers or numbers with a comparison method in the form of systematic calculations, which are based on calculations or relevant formulas contained in the EVA concept. The results of research in 2014-2018 EVA PT ABC experienced fluctuations. On average PT. ABC can be said to have enough added value because the net profit after tax generated is greater than the cost of capital. And when compared with the standard, PT. ABC can be said to be good because of the positive EVA value. Suggestions given for this are the results that have been obtained from calculations using Economic Value Added (EVA) analysis should be able to encourage companies to continue to increase the value of the company so that it becomes better in the future. And for further researchers who want to conduct similar research, it is hoped that it should combine financial ratio analysis to assess the company's financial performance in terms of the company's operations, and also the Economic Value Added (EVA) method as a supporter of financial ratio analysis.